THE EFFECT OF DIGITAL TRANSFORMATION ON THE EFFECTIVENESS OF INTERNAL AUDITING AND FRAUD PREVENTION IN MODERN ORGANIZATIONS: A SYSTEMATIC LITERATURE REVIEW - Agretta Thalia Kamba; Suci Rahmatia S. Umar; Qistiatun Adilla Neu; Rislan R. Ali; Sahmin Noholo (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Digital transformation is the process of bringing technology into the work of organisations. The main goal is to make things work better, be more open and make decisions. Internal audits are important to make sure organisations are running smoothly and safely. This means audits need to be able to watch over control and manage risks properly. This is very important for organisations to achieve their goals. Stopping fraud is about finding and preventing actions that can hurt the organisation. This research is trying to figure out how digital transformation affects audits and stopping fraud. The researchers used a method called a 'systematic literature review'. This research is about describing things in detail. They got their information from international journals. They used Google Scholar, Scopus and Sinta to find articles from 2022 to 2025. What they found out is that technology like intelligence looking at data, blockchain, robotic process automation and electronic auditing can make internal audits better. These technologies can also make things more transparent. Help stop fraud. However, digital transformation is not easy to do. There are some problems, like auditors not being good enough with technology risks to cybersecurity and organisations not being ready. Digital transformation and internal audits are. Digital transformation can affect fraud prevention. Digital transformation is important for organisations. It can help with internal audits and fraud prevention.